Motivation States for Physical Activity and Sedentary Behavior: Desire, Urge, Wanting, and Craving. - Stults-Kolehmainen, Matthew A; Blacutt, Miguel; Bartholomew, John B; Gilson, Todd A; Ash, Garrett I; McKee, Paul C; Sinha, Rajita (Frontiers in psychology, 2020)
To better explain daily fluctuations in physical activity and sedentary behavior, investigations of motivation are turning from social cognitive frameworks to those centered on affect, emotion and automaticity, such as the Affect and Health Behavior Framework (AHBF), Integrated Framework and Affective-Reflective Theory (ART). This shift has necessitated: (a) re-examination of older theories and their constructs, such as drives, needs and tensions and (b) an inspection of competing theories from other fields that also attempt to explain dynamic changes in health behaviors. The Dynamical Model of Desire, Elaborated Intrusion Theory and others commonly share with AHBF the idea that human behavior is driven strongly by desires and/or the similar concepts of wants, urges, and cravings. These affectively-charged motivation states (ACMS) change quickly and may better explain physical activity behavior from one moment to the next. Desires for movement predominantly derive from negative but also positive reinforcement. Data from clinical populations with movement dysfunction or psychiatric disorders provides further evidence of these drivers of movement. Those with Restless Legs Syndrome, akathisia, tic disorders and exercise dependence all report strong urges to move and relief when it is accomplished. Motor control research has identified centers of the brain responsible for wants and urges for muscular movement. Models elaborated herein differentiate between wants, desires, urges and cravings. The WANT model (Wants and Aversions for Neuromuscular Tasks) conceptualizes desires for movement and rest as varying by magnitude, approach or avoidance-orientation (wants versus aversions) and as occupying independent dimensions instead of opposite ends of the same axis. For instance, one hypothetically might be in a state of both high desire for movement and rest simultaneously. Variations in motivation states to move and rest may also be associated with various stress states, like freezing or fight and flight. The first validated instrument to measure feelings of desire/want for movement and rest, the CRAVE Scale (Cravings for Rest and Volitional Energy Expenditure) is already shedding light on the nature of these states. With these advances in theory, conceptual modeling and instrumentation, future investigations may explore the effects of desires and urges for movement and sedentary behavior in earnest. Copyright © 2020 Stults-Kolehmainen, Blacutt, Bartholomew, Gilson, Ash, McKee and Sinha.
Keywords: conceptual analysis; dept.psy; desire; exercise; motivation; motivation states; peer-reviewed; physical activity; sedentary activity; urge for movement

Feasibility and safety of a group physical activity program for youth with type 1 diabetes - Ash, Garrett I.; Joiner, Kevin L.; Savoye, Mary; Baker, Julien S.; Gerosa, James; Kleck, Emma; Patel, Neha S.; Sadler, Lois S.; Stults-Kolehmainen, Matthew; Weinzimer, Stuart A.; Grey, Margaret (Pediatric Diabetes, 2019)
Background/ObjectiveMany adolescents with type 1 diabetes do not achieve 60 minutes of daily moderate-to-vigorous intensity physical activity (MVPA). Recognizing the importance of peer influence during adolescence, we evaluated the feasibility and safety of a group MVPA intervention for this population. MethodsEighteen adolescents with type 1 diabetes (age 14.12 .3 years, female 67%, black or Latino 67%, median body mass index 92%ile, A1c 79.925.1 mmol/mol, 9.5 +/- 2.3%). Intervention sessions (35minutes MVPA and 45minutes discussion) occurred 1x/week for 12weeks. Feasibility and safety metrics were enrollment, completion of intervention and assessments, cost, and hypoglycemia rates. Participants completed MVPA (accelerometry), and exploratory nutritional, psychosocial, clinical, and fitness variable assessments at baseline, 3 months, and 7 months. Hedges' effect sizes were calculated. ResultsEnrollment was 16%, and intervention completion was 56%. Assessment completion at 7 months was 67% for MVPA, nutrition, and fitness, 83% for psychosocial assessments, and 94% for clinical assessments. Cost was $1241 per completing participant. One episode of mild hypoglycemia occurred during the sessions (0.6%). Self-reported daily fruit/vegetable servings (d=-0.72) and diabetes self-management behaviors decreased over time (d=-0.40). In the 10 completers, endurance run score improved (d=0.49) from low baseline levels, while systolic blood pressure decreased (d=-0.75) and low-density lipoprotein increased (d=0.49) but stayed within normal ranges. ConclusionsThe protocol for the group MVPA intervention was safe and had some feasibility metrics meriting further investigation. MVPA levels and glycemic control remained suboptimal, suggesting the need for more intensive interventions for this population.
Keywords: Accelerometry; Adolescent; Age Factors; Article; Black person; Blood Glucose; Child; Combined Modality Therapy; Diabetes Mellitus, Type 1; Diet Records; Exercise; Exercise Therapy; Feasibility Studies; Female; Group Processes; Health Behavior; Hispanic; Humans; Male; Young Adult; accelerometry; adolescent; adult; adverse event; age; behavior; blood; body mass; child; clinical article; clinical outcome; clinical protocol; clinical trial; cost; dept.hms; diabetes mellitus; disease severity; endurance; exercise; feasibility study; female; fitness; food intake; fruit; glucose blood level; glycated hemoglobin A; group process; health behavior; health program; human; hypoglycemia; insulin dependent diabetes mellitus; kinesiotherapy; low density lipoprotein; male; medical record; metabolism; multimodality cancer therapy; nutritional assessment; patient safety; peer-reviewed; physical activity; physiology; priority journal; procedures; psychosocial care; scoring system; self care; self report; systolic blood pressure; type 1; vegetable; young adult

College community–based physical activity support at a public university during the COVID-19 pandemic: retrospective longitudinal analysis of intra- versus interpersonal components for uptake and outcome association - Ash, Garrett; Mak, Selene; Haughton, Adrian; Augustine, Madilyn; Bodurtha, Phillip; Axtell, Robert; Borsari, Beatrice; Liu, Jason; Lou, Shaoke; Xin, Xin; Fucito, Lisa; Jeon, Sangchoon; et al. (JMIR mhealth and uhealth, 2025)
Background College students are vulnerable to setting long-term trajectories of low physical activity (PA) but are reachable via mobile health fitness tracking (eg, mobile health step counting) and interpersonal support tailored to the college community. However, no studies have statistically isolated the appeal and influence of these intra- and interpersonal components in college-based PA interventions. Objective This study retrospectively examined a college-based PA promotion program at a northeast US public university during the COVID-19 pandemic to (1) test the impact of student status on the use of intervention components and (2) determine whether such use was associated with successful retention and goal achievement in the program. Methods The university used a commercial platform for a 30-day PA promotion program during April 2021 with intrapersonal (step-tracker syncing, education, self-monitoring, and motivational messaging) and interpersonal (friend interactions and team games) components. App use was operationalized as intrapersonal (frequency of opening app, education, and self-monitoring) and interpersonal (friends made in-app and team affiliation and size). Results Campus-wide emails elicited sign-up by 156 undergraduate students, 57 graduate students, and 126 faculty and staff members. Objective 1 yielded the following results: undergraduates used the app less frequently (median 0.8, IQR 0.4-1.7 times per day) than other groups (graduate students: median 1.4, IQR 0.7-2.7 times per day; P=.01; faculty: median 1.3, IQR 0.7-2.7 times per day, H2=14.5; P=.001) but made the same number of friends (median 1-2) and teammates (median 8-9; P=.77 for friends and P=.93 for teammates). Objective 2 yielded the following results: most participants (313/335, 93.4%; 95% CI 90%-96%) were retained for the first 7 days, but by 30 days, retention dropped, most notably for undergraduate students (82/154, 53.2%; 95% CI 45%-61%), followed by graduate students (39/56, 70%; 95% CI 56%-81%) and faculty and staff (93/125, 74.4%; 95% CI 66%-82%; χ22=12.6; P<.001). Retention was associated with app engagement frequency (model hazard ratio 0.56, 95% CI 0.43-0.72; P<.001) and affiliation with a team having high median app engagement and a large size (intracluster correlation coefficient 0.064, 95% CI 0.001-0.164, P=.05). Meeting a daily step goal was associated with app engagement frequency (β=.72, SE=0.21; P=.001), number of friends (β=.40, SE 0.20; P=.04), and an initial motive of maintaining or increasing (rather than starting) PA (β=.99, SE=0.21; P<.001). Conclusions College students, compared with faculty and staff, used the app less frequently, used the app for a shorter duration before abandonment, and met the step goal on fewer days. Engagement with the program was associated with longer retention and better PA outcomes, which were critically modified by the interpersonal engagement. These findings suggest that college students using virtual PA support during times of physical isolation could benefit from more tailored implementation strategies (eg, timed prompts and team reassignments).
Keywords: Computer science; Coronavirus disease 2019 (COVID-19); Demography; Disease; Gerontology; Infectious disease (medical specialty); Internal medicine; Medicine; Preprint; Sociology; dept.hms

Testing multiple delivery methods of the virtual exercise games for youth with T1D peer intervention: protocol development and feasibility - Ash, Garrett; Nam, Soohyun; Mak, Selene; Stults-Kolehmainen, Matthew; Haughton, Adrian; Turek, Carolyn; Baker, Julien; Hieftje, Kimberly; Marks, Asher; Chmielewski, Annette; Shelver, Michael; Considine, Elizabeth; et al. (Hormone Research in Paediatrics, 2026)
INTRODUCTION: Adolescents with type 1 diabetes (T1D) face barriers to moderate-to-vigorous physical activity (MVPA) such as uncertainty with self-management, limited access to supportive environments, and stigma related to living with diabetes. Opportunities for peer activities with T1D role model support are limited. To address this need, we tested iterative refinements of pilot Virtual Exercise Games for Youth with T1D (ExerT1D) for feasibility and acceptability. METHODS: The program included 6 versions: study 1 (1.1-1.4) included an active video game, and study 2 (2.1-2.2) included a virtual reality (VR) active video game. All versions included T1D exercise management education by clinicians and goal-setting guided by young adult coaches with T1D. RESULTS: Seventeen adolescents (median age 15.4 [IQR 14.6-16.4] years, 7 non-Hispanic white, 8 male, median HbA1c 8.1% [IQR 7.4%-11.1%]) were enrolled. Participants rated the program, comfort, clinicians, coaches, and group cohesion high/very high. Motivation for the video game was high. Building T1D and MVPA self-management skills was rated excellent at most sessions, as were peer interactions and enriched communication after adding immersive VR in study 2. Transitions between VR apps caused delays of 19 ± 6 min per 60 min-90 min session. Compared to baseline, HbA1c or glucose management indicator decreased over time in an exploratory analysis (d = -1.12, 90% CI: [-1.78, -0.48]). CONCLUSIONS: In a small cohort, the ExerT1D program facilitated a supportive environment for engaging diverse youth with T1D in an MVPA program led by T1D coaches. Larger studies are needed to assess the intervention's impact on engagement with physical activity, glycemic outcomes, and quality of life.
Keywords: Glycemic; Physical activity; Program evaluation; Protocol (science); Quality (philosophy); Quality of life (healthcare); dept.hms

Establishing a global standard for wearable devices in sport and fitness: Perspectives from the new england chapter of the american college of sports medicine members. - Ash, Garrett I.; Stults-Kolehmainen, Matthew A.; Busa, Michael A.; Gregory, Robert; Garber, Carol Ewing; Liu, Jason; Gerstein, Mark; Casajús, José A.; González-Agüero, A.; Constantinou, Demitri; Geistlinger, Michael; Guppy, Fergus M.; et al. (Current sports medicine reports, 2020)
The recent explosion of wearable technology and the associated concerns prompted the International Federation of Sports Medicine (FIMS) to create a quality assurance standard for wearable devices, which provides commissioned testing of marketing claims and endorsement of commercial wearables that test favorably. An open forum as announced in the conference advertising was held at the Annual Meeting of the New England Regional Chapter of the American College of Sports Medicine (NEACSM) November 7 to 8, 2019, in Providence, Rhode Island, USA for attending NEACSM members to voice their input on the process. Herein, we report the proceedings. The round table participants perceived the quality assurance standard to be important, but identified some practical process challenges that included the broad scope and complexity of the device universe, the need for a multiphase testing pathway, and the associated fees for product evaluation. The participants also supported the evaluation of device data analysis, behavioral influences, and user experience in the overall evaluation. Looking forward, the FIMS quality assurance standard faces the challenge of balancing these broader perspectives with practical constraints of budget, facilities, time, and human resources. © 2020 by the American College of Sports Medicine.
Keywords: Fitness Trackers; Humans; New England; Sports; Sports Medicine; United States; Wearable Electronic Devices; activity tracker; adult; article; budget; cosmos; data analysis; dept.hms; electronic device; human; peer-reviewed; quality control; sport; sports medicine

Measurement of Motivation States for Physical Activity and Sedentary Behavior: Development and Validation of the CRAVE Scale. - Stults-Kolehmainen, Matthew A; Blacutt, Miguel; Fogelman, Nia; Gilson, Todd A; Stanforth, Philip R; Divin, Amanda L; Bartholomew, John B; Filgueiras, Alberto; McKee, Paul C; Ash, Garrett I; Ciccolo, Joseph T; Brotnow Decker, Line; et al. (Frontiers in psychology, 2021)
Physical activity, and likely the motivation for it, varies throughout the day. The aim of this investigation was to create a short assessment (CRAVE: Cravings for Rest and Volitional Energy Expenditure) to measure motivation states (wants, desires, urges) for physical activity and sedentary behaviors. Five studies were conducted to develop and evaluate the construct validity and reliability of the scale, with 1,035 participants completing the scale a total of 1,697 times. In Study 1, 402 university students completed a questionnaire inquiring about the want or desire to perform behaviors "at the present moment (right now). " Items related to physical activity (e.g., "move my body") and sedentary behaviors (e.g., "do nothing active"). An exploratory structural equation model (ESEM) revealed that 10 items should be retained, loading onto two factors (5 each for Move and Rest). In Study 2, an independent sample (n = 444) confirmed these results and found that Move and Rest desires were associated with stage-of-change for exercise behavior. In Study 3, 127 community-residing participants completed the CRAVE at 6-month intervals over two years- two times each session. Across-session interclass correlations (ICC) for Move (ICC = 0.72-0.95) and Rest (ICC = 0.69-0.88) were higher than when they were measured across 24-months (Move: ICC = 0.53; Rest: ICC = 0.49), indicating wants/desires have state-like qualities. In Study 4, a maximal treadmill test was completed by 21 university students. The CRAVE was completed immediately pre and post. Move desires decreased 26% and Rest increased 74%. Changes in Move and Rest desires were moderately associated with changes in perceived physical fatigue and energy. In Study 5, 41 university students sat quietly during a 50-min lecture. They completed the CRAVE at 3 time points. Move increased 19.6% and Rest decreased 16.7%. Small correlations were detected between move and both perceived energy and tiredness, but not calmness or tension. In conclusion, the CRAVE scale has good psychometric properties. These data also support tenets of the WANT model of motivation states for movement and rest (Stults-Kolehmainen et al., 2020a). Future studies need to explore how desires to move/rest relate to dynamic changes in physical activity and sedentarism. Copyright © 2021 Stults-Kolehmainen, Blacutt, Fogelman, Gilson, Stanforth, Divin, Bartholomew, Filgueiras, McKee, Ash, Ciccolo, Brotnow Decker, Williamson and Sinha.
Keywords: dept.psy; peer-reviewed

Testing Multiple Delivery Methods of the Virtual Exercise Games for Youth with T1D Peer Intervention: Protocol Development and Feasibility - Ash, Garrett I.; Nam, Soohyun; Mak, Selene S.; Stults-Kolehmainen, Matthew; Haughton, Adrian D.; Turek, Carolyn; Baker, Julien S.; Hieftje, Kimberly; Marks, Asher; Chmielewski, Annette; Shelver, Michael; Considine, Elizabeth G.; et al. (Hormone Research in Paediatrics, 2026)
Abstract – Introduction: Adolescents with type 1 diabetes (T1D) face barriers to moderate-to-vigorous physical activity (MVPA) such as uncertainty with self-management, limited access to supportive environments, and stigma related to living with diabetes. Opportunities for peer activities with T1D role model support are limited. To address this need, we tested iterative refinements of pilot Virtual Exercise Games for Youth with T1D (ExerT1D) for feasibility and acceptability. Methods: The program included 6 versions: study 1 (1.1–1.4) included an active video game, and study 2 (2.1–2.2) included a virtual reality (VR) active video game. All versions included T1D exercise management education by clinicians and goal-setting guided by young adult coaches with T1D. Results: Seventeen adolescents (median age 15.4 [IQR 14.6–16.4] years, 7 non-Hispanic white, 8 male, median HbA1c 8.1% [IQR 7.4%–11.1%]) were enrolled. Participants rated the program, comfort, clinicians, coaches, and group cohesion high/very high. Motivation for the video game was high. Building T1D and MVPA self-management skills was rated excellent at most sessions, as were peer interactions and enriched communication after adding immersive VR in study 2. Transitions between VR apps caused delays of 19 ± 6 min per 60 min–90 min session. Compared to baseline, HbA1c or glucose management indicator decreased over time in an exploratory analysis (d = −1.12, 90% CI: [−1.78, −0.48]). Conclusions: In a small cohort, the ExerT1D program facilitated a supportive environment for engaging diverse youth with T1D in an MVPA program led by T1D coaches. Larger studies are needed to assess the intervention’s impact on engagement with physical activity, glycemic outcomes, and quality of life. © 2026 S. Karger AG, Basel
Keywords: Diabetes; Peer support; Physical activity; Type 1; Video games; dept.hms

Establishing a global standard for wearable devices in sport and exercise medicine: Perspectives from academic and industry stakeholders - Ash, Garrett I.; Stults-Kolehmainen, Matthew; Busa, Michael A.; Gaffey, Allison E.; Angeloudis, Konstantinos; Muniz-Pardos, Borja; Gregory, Robert; Huggins, Robert A.; Redeker, Nancy S.; Weinzimer, Stuart A.; Grieco, Lauren A.; Lyden, Kate; et al. (Sports medicine (Auckland, N.Z.), 2021)
Millions of consumer sport and fitness wearables (CSFWs) are used worldwide, and millions of datapoints are generated by each device. Moreover, these numbers are rapidly growing, and they contain a heterogeneity of devices, data types, and contexts for data collection. Companies and consumers would benefit from guiding standards on device quality and data formats. To address this growing need, we convened a virtual panel of industry and academic stakeholders, and this manuscript summarizes the outcomes of the discussion. Our objectives were to identify (1) key facilitators of and barriers to participation by CSFW manufacturers in guiding standards and (2) stakeholder priorities. The venues were the Yale Center for Biomedical Data Science Digital Health Monthly Seminar Series (62 participants) and the New England Chapter of the American College of Sports Medicine Annual Meeting (59 participants). In the discussion, stakeholders outlined both facilitators of (e.g., commercial return on investment in device quality, lucrative research partnerships, and transparent and multilevel evaluation of device quality) and barriers (e.g., competitive advantage conflict, lack of flexibility in previously developed devices) to participation in guiding standards. There was general agreement to adopt Keadle et al.’s standard pathway for testing devices (i.e., benchtop, laboratory, field-based, implementation) without consensus on the prioritization of these steps. Overall, there was enthusiasm not to add prescriptive or regulatory steps, but instead create a networking hub that connects companies to consumers and researchers for flexible guidance navigating the heterogeneity, multi-tiered development, dynamicity, and nebulousness of the CSFW field. © 2021, The Author(s), under exclusive licence to Springer Nature Switzerland AG.
Keywords: Consensus; Exercise; Humans; Sports; Sports Medicine; United States; Wearable Electronic Devices; adult; article; consensus; consumer; data science; dept.hms; electronic device; exercise; female; human; human experiment; investment; major clinical study; male; sport; sports medicine